2020
DOI: 10.1038/s41419-020-03204-3
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone (CRH) alters mitochondrial morphology and function by activating the NF-kB-DRP1 axis in hippocampal neurons

Abstract: Neuronal stress-adaptation combines multiple molecular responses. We have previously reported that thorax trauma induces a transient loss of hippocampal excitatory synapses mediated by the local release of the stress-related hormone corticotropin-releasing hormone (CRH). Since a physiological synaptic activity relies also on mitochondrial functionality, we investigated the direct involvement of mitochondria in the (mal)-adaptive changes induced by the activation of neuronal CRH receptors 1 (CRHR1). We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 77 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…Several studies have linked DRP1-mediated mitochondrial fission to activation of NF-κB, thus linking increased DRP1 expression with an enhanced inflammatory response to various stimuli in multiple cell types [ 50 , 51 , 52 ]. There is, however, a lack in understanding of the role DRP1 plays in inflammation initiated by airway epithelial cells in response to allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked DRP1-mediated mitochondrial fission to activation of NF-κB, thus linking increased DRP1 expression with an enhanced inflammatory response to various stimuli in multiple cell types [ 50 , 51 , 52 ]. There is, however, a lack in understanding of the role DRP1 plays in inflammation initiated by airway epithelial cells in response to allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked DRP1-mediated mitochondrial ssion to activation of NF-κB, thus linking increased DRP1 expression with an enhanced in ammatory response to various stimuli in multiple cell types (50)(51)(52). There is, however, a lack in understanding of the role DRP1 plays in in ammation initiated by airway epithelial cells in response to allergen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reported in hippocampal neurons hypoxia-induced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1 α ( Figure 6(a) ), which was consistent with previous publications carried out in fibroblasts [ 30 ], cardiac cells [ 22 ], and vascular smooth muscle cells [ 34 ]. Although other transcription factors such as Smad2/3 [ 35 ], NF- κ B [ 36 ], and calcium-related transcription factors [ 37 ] have been reported to correlate with Drp1 expression, we demonstrated that HIF-1 α inhibitors could almost completely inhibit hypoxia-induced Drp1 expression ( Figure 6(b) ), and thus, suggesting the pivotal role of HIF-1 α .…”
Section: Discussionmentioning
confidence: 64%
“…Although other transcription factors such as Smad2/3 [35], NF-κB [36], and calcium-related transcription factors [37] have been reported to correlate with Drp1 expression, we demonstrated that HIF-1α inhibitors could almost completely inhibit hypoxia-induced Drp1 expression (Figure 6 Figure 7: Hypoxia-and propofol-modulated phosphorylation of Drp1 and mitochondrial dynamics was mediated via ERK and PKA pathway. The upper panel was a representative experiment, and the lower panel was the summary of densitometric data from 5 separate experiments.…”
mentioning
confidence: 76%